1D symmetry for semilinear PDEs from the limit interface of the solution. Issue 4 (2nd April 2016) - Farina, Alberto; Valdinoci, Enrico
ABSTRACT: We study bounded, monotone solutions of Δ u  =  W ′( u ) in the whole of ℝ n, where W is a double-well potential. We prove that under suitable assumptions on the limit interface and on the energy growth, u is 1D. In particular, differently from the previous literature, the solution is not assumed to have minimal properties and the cases studied lie outside the range of Γ-convergence methods. We think that this approach could be fruitful in concrete situations, where one can observe the phase separation at a large scale and wishes to deduce the values of the state parameter in the vicinity of the interface. As a simple example of the results obtained with this point of view, we mention that monotone solutions with energy bounds, whose limit interface does not contain a vertical line through the origin, are 1D, at least up to dimension 4.